MODIFIKASI SILIKA GEL DARI ABU LIMBAH HASIL PROSES PEMBAKARAN INDUSTRI BATU BATA DENGAN DIFENILKARBAZON SEBAGAI ADSORBEN SERTA UJI DAYA SERAP TERHADAP ION LOGAM Cr(III) DAN Cu(II) - Sudiarta, I. W.; Saputra, I G. D. V.; Suarya, P. (Jurnal Kimia (Journal of Chemistry), 2022)
The modification of silica gel, from the waste of the bricks burning process, with diphenylcarbazone has been done. The silica gel modified by diphenylcarbazone (Si-DPZon) was obtained by boiling the ash with NaOH solution to create sodium silicate and neutralized with HCl to get the silica gel, then physically modified with diphenylcarbazone ligand. The study included the determination of the adsorbent functional groups by spectrophotometer IR, surface acidity by acid-base titration method, specific surface area by absorption of methylene blue method, the optimum conditions (pH, contact time) of the adsorption of Cr(III) and Cu(II). FTIR analysis showed that the Si-DPZon contained amide (N-H), carbonyl (C=O), silanol (Si-OH), siloxane (Si-O-Si) and aromatic (C-H) functional groups. The results showed that Si-DPZon had a surface acidity (K al ) of 5.8384 ± 0.2466 mmol/g with the number of active sites of 12.3945x10 20  atom/g with a specific surface area of 12.6886 m 2 /g. Si-ABB had a surface acidity (K al ) of 4.5568±0,2453 mmol/g with the number of active sites of 27.4410x10 20  atom/g and with a specific surface area of 11.6712 m 2 /g. The optimum conditions for adsorption of chromium (III), both Si-DPZon and Si-ABB occurred at pH 5 and 15 minutes. The adsorption ability of Cr(III) by Si-DPZon at the pH and contact time optimum conditions was 34.6927 mg/g with an adsorption percentage of 86.7317% and Si-ABB was obtained at 34.5445 mg/g with the adsorption percentage of 86.3611%. Adsorption ability of Cu(II) by Si-DPZon at the pH and contact time optimum conditions was 26.49672 mg/g with the adsorption percentage of 66.2418% and Si- ABB was obtained at 24.93210 mg/g with the adsorption percentage of 62.3302%. Keywords:     adsorptions, chromium (III), copper (II), diphenilcarbazone ligand, synthesis of silica gel.